Preventing diabetic foot ulcer recurrence in high-risk patients: use of temperature monitoring as a self-assessment tool - Constantinides, Georgios; Higgins, Kevin R.; Lanctot, Dan R. (My University, 2007)
OBJECTIVE - The purpose of this study was to evaluate the effectiveness of a temperature monitoring instrument to reduce the incidence of foot ulcers in individuals with diabetes who have a high risk for lower extremity complications. RESEARCH DESIGN AND METHODS - In this physician-blinded, randomized, 15-month, multicenter trial, 173 subjects with a previous history of diabetic foot ulceration were assigned to standard therapy, structured foot examination, or enhanced therapy groups. Each group received therapeutic footwear, diabetic foot education, and regular foot care. Subjects in the structured foot examination group performed a structured foot inspection daily and recorded their findings in a logbook. If standard therapy or structured foot examinations identified any foot abnormalities, subjects were instructed to contact the study nurse immediately. Subjects in the enhanced therapy group used an infrared skin thermometer to measure temperatures on six foot sites each day. Temperature differences >4°F (>2.2°C) between left and right corresponding sites triggered patients to contact the study nurse and reduce activity until temperatures normalized. RESULTS - The enhanced therapy group had fewer foot ulcers than the standard therapy and structured foot examination groups (enhanced therapy 8.5 vs. standard therapy 29.3%, P = 0.0046 and enhanced therapy vs. structured foot examination 30.4%, P = 0.0029). Patients in the standard therapy and structured foot examination groups were 4.37 and 4.71 times more likely to develop ulcers than patients in the enhanced therapy group. CONCLUSIONS - Infrared temperature home monitoring, in serving as an "early warning sign," appears to be a simple and useful adjunct in the prevention of diabetic foot ulcerations.
Keywords: Clinical trials; Patient compliance; Temperature measurements; Patient education